The Effect of Capital Structure and Litigation Risk on Accounting Prudence - Wibowo, Jessica Laurentin; Aminah, Aminah (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the influence of capital structure and litigation risk on the implementation of prudent accounting in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The principle of prudent accounting is crucial in the banking sector given the high level of risk, strict regulations, and demands for transparency and reliability of financial reports. This study uses a quantitative approach with library research and documentation techniques. The data used are secondary data in the form of annual financial reports of banking companies obtained from the official IDX website and the official websites of each company. The sample was determined using a purposive sampling method based on certain criteria: banking companies listed on the Indonesia Stock Exchange (IDX) during the study period, having been public companies for at least 15 years, and publishing complete and consecutive financial reports during the 2022–2024 period. Data analysis was performed using multiple linear regression with the aid of statistical software. The results show that capital structure influences prudent accounting, with companies with a certain scale and funding structure tending to demonstrate a lower level of prudence in financial reporting. Furthermore, litigation risk also influences prudent accounting, indicating that the higher the risk of lawsuits faced by a company, the lower the tendency of management to apply prudent accounting principles. These findings imply that financial characteristics and external pressures play a significant role in determining the level of accounting prudence in the banking sector.